2006
DOI: 10.1093/ije/dyl167
|View full text |Cite
|
Sign up to set email alerts
|

Childhood diarrhoea management practices in Bangladesh: private sector dominance and continued inequities in care

Abstract: Households seeking help from a health provider overwhelmingly utilize the private sector in Bangladesh. Gender inequities in the utilization of licensed providers and purchase of antibiotics, favouring males were identified. Findings suggest that higher income, urban households tend to practice greater gender discrimination. In order to better understand health dynamics in urban populations, in particular slum-dwellers, there is a need to disaggregate survey data by household location.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 16 publications
2
55
0
2
Order By: Relevance
“…The quality of care at private health facilities may also vary by income. 52 Among patients who can afford care, those with lower income may not receive as high level of care as those with higher income.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of care at private health facilities may also vary by income. 52 Among patients who can afford care, those with lower income may not receive as high level of care as those with higher income.…”
Section: Discussionmentioning
confidence: 99%
“…63,64 Perhaps tellingly it is also omitted in the conceptual framework of the WHO Commission on Social Determinants of Health. 57 Studies to date have focused mainly on household-level disparities by socioeconomic or rural/urban status [65][66][67][68] or individual-(including intrahousehold-) level differences by gender or children's age. [69][70][71][72] With one or two exceptions, 47,71 no research has directly examined the role of (old) age as a determinant of differential healthcare access.…”
Section: Impacts On Progress Towards Achieving the Mdgsmentioning
confidence: 99%
“…A study from Bangladesh displayed a similar pattern, finding that lower income children were more likely to seek treatment of diarrhea at unlicensed providers, and as a result, was less likely to receive ORT. 30 Another study from Lao found that facilities visited by poorer patients were less capable of providing diagnostics, examinations, or appropriate advice. 31 Recently, the global health community has emphasized the role of the private sector in filling voids in health care where the public sector is inadequate.…”
Section: Discussionmentioning
confidence: 99%